A robust framework of hydraulic fracturing applications for competent roof caving in underground longwall operations - Wu, Xiaoru; Gu, Wenzhe; He, Qingyuan; Gao, Xuefeng; Liu, Benben; Li, Qiang; Yang, Yang; Gong, Yanchuan (Frontiers in Earth Science, 2025)
Longwall working faces are considered one of the main technological methods for large-scale coal mining projects, as they enable the extraction of more coal resources in a single operation. However, the large-scale cantilever roof formed in scenarios with hard rock layers presents significant challenges to mining safety operations. Managing the hard-hanging roof to control the risks of rock bursts and coal and gas outbursts is a key scientific issue that longwall working faces must overcome. To address this, we propose a comprehensive hydraulic fracturing technology framework for managing the hard, suspended roof, using the 51,212 working face of the Guojiawan Coal Mine as a case study. Rock mechanics tests were conducted to determine the mine’s geotechnical and geological conditions. A robust 3DEC numerical simulation was performed to develop the optimal design for hydraulic fracturing, particularly identifying the locations where fracturing should occur. Finally, a comprehensive field application of the hydraulic fracturing technique was conducted, with extensive site monitoring. The results demonstrated that hydraulic fracturing in the middle of the goaf area produced the best caving outcomes, with the roof collapsing after the longwall face retreated by 130 m. The field monitoring data—such as rockbolt stress, tunnel convergence, and hydraulic shield pressure—validated the numerical simulation results. As a result, a validated framework for hydraulic fracturing at field scale was developed, providing guidance for future engineering applications.